Agricultural machinery and tools in Mesopotamia - Khadim Tahir, Ahmed; Mansour Muhamad, Fatin (Al-Adab Journal, 2019)
When the man appeared in the northern part of Mesopotamia, since the Paleolithic period he lived in the caves, relying on food to collect food from plants, wild grasses and hunting the animals with primitive stone tools and tools, some of them for hunting and some for precision and some for scraping. The ax was used until the Stone Age (15000-10000 BC). After the improvement of the climate, this man began to migrate to the open areas and be the first population groupings at the site of Zawey Jamie, Mulfaat and Karim Shahr . Are seasonal and not permanent settlements. The middle stone age is the first beginning of primitive agriculture due to the first population group. It also promised the first start of the production of the food after it was a collector of oil and also some of the animals. In this age, its machines and stone tools evolved. The tools of grinding, crushing, Neolithic (about 10000 BC) developed the idea of ​​mass settlement, which led to the emergence of the first villages of agricultural populations in northern Mesopotamia, such as Gramo, Hassouna and Tall AL-Sowan, Where agriculture and animals were condemned, and the emergence of these agricultural villages led to the development of the idea of ​​crop production It was developed over the years as the agricultural lands expanded with the expansion of the settlement villages since the fifth millennium BC, as this agriculture required the creation of new agricultural tools that meet the required purpose of Production and harvest of many agricultural crops, so agricultural machinery passed several stages of development contributed to the arrival of the summit of the development of agriculture and its success in those ages. The agricultural machinery was of great importance in Mesopotamia, and this importance came through the religious character of some of these machines represented by the symbols of several gods, As the plow symbolizes the god Shamsh and the god of Nanorata, and the survey is a symbol of the god Shamsh, and the shovel symbolizes the god of Merodok, and the ax is a symbol of the god Add . In this paper, we will examine agricultural machinery for its importance in the development of agriculture in Mesopotamia and include agricultural machinery used in irrigation and harvesting.